2006
DOI: 10.1002/neu.20286
|View full text |Cite
|
Sign up to set email alerts
|

Gβγ that interacts with adenylyl cyclase in opioid tolerance originates from a Gs protein

Abstract: We previously demonstrated that chronic morphine induces a change in G protein coupling by the mu opioid receptor (MOR) from Gi/o to Gs, concurrent with the instatement of an interaction between Gbetagamma and adenylyl cyclase types II and IV. These two signaling changes confer excitatory effects on the cell in place of the typical inhibition by opioids and are associated with morphine tolerance and dependence. Both signaling changes and these behavioral manifestations of chronic morphine are attenuated by cot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 37 publications
(44 reference statements)
4
24
0
Order By: Relevance
“…After longterm treatment with morphine (twice-daily injections of 10 mg/kg morphine for 7 days), there is a switch from the inhibitory G␣ i/o coupling to the stimulatory G␣ s coupling in all three brain regions. Moreover, the switch in the G␣ subunit coupling is associated with a stimulation of adenylyl cyclases (Wang et al, 2005;Wang and Burns, 2006). These studies not only provide evidence for a switch in G␣ coupling but also illustrate how morphine-mediated OR coupling can differ depending upon the tissue in which it is expressed.…”
Section: Biased Agonism With Respect To G Protein Couplingmentioning
confidence: 70%
“…After longterm treatment with morphine (twice-daily injections of 10 mg/kg morphine for 7 days), there is a switch from the inhibitory G␣ i/o coupling to the stimulatory G␣ s coupling in all three brain regions. Moreover, the switch in the G␣ subunit coupling is associated with a stimulation of adenylyl cyclases (Wang et al, 2005;Wang and Burns, 2006). These studies not only provide evidence for a switch in G␣ coupling but also illustrate how morphine-mediated OR coupling can differ depending upon the tissue in which it is expressed.…”
Section: Biased Agonism With Respect To G Protein Couplingmentioning
confidence: 70%
“…Increased agonist potency may simply increase the number of bg subunits after activation of the G i -protein. In addition, several studies have also provided evidence that the m-opioid receptor couples to the G as subtype after chronic morphine pretreatment (Chakrabarti et al, 1998(Chakrabarti et al, , 2005Wang and Burns, 2006). GIRK channels are directly activated by bg subunits (Huang et al, 1995), so an increase in bg release after increased excitatory G as signaling mediated by m-opioid receptors could also increase activation of GIRK channels.…”
Section: Discussionmentioning
confidence: 99%
“…There are 23 studies in isolated membranes or whole cells overexpressing AC2 that document this activation, and some of these are very frequently cited Federman et al1992). An additional four studies show direct Gbg binding to AC2, and this has also been reported in endogenous expression systems (Wang et al 2005;Wang and Burns 2006). In stark contrast, there is much less evidence for the activation of AC4 by Gbg subunits, with only two studies conducted in overexpression systems (Gao and Gilman 1991;Marjamaki et al 1997).…”
Section: Indirect Ca 21 Regulation Via Gbgmentioning
confidence: 95%